Indice de inadimplência SERASA: um estudo de séries temporais - Peixoto, Marcelo Ferreira (2009)
With the improvement in income class C in Brazil since 2000 and a growing consumption of goods and services, there was a large increase in the number of people who had access to credit and thus the need for family financial planning. In this framework the evolution of default of individuals is central to the decisions of the credit business and economic developments in the country This work contributes through the use of econometric techniques such as unit root test, cointegration tests of Trace and Maximum Eigenvalue to explore the relationship between the volume of retail sales, the INPC (National Index of Consumer Price), number of workers with formal jobs and the Selic rate and default rate SERASA. The model results indicate that all explanatory variables have a positive correlation with the explanatory variable.